The N2 second positive (C3Πu → B3Πg) system reviewed: Improved data and analysis. (December 2019) - Ventura, Laiz R.; Fellows, C.E.
Highlights: Larger number of bands ever analysed in Fourier transform spectroscopy in this band. Potential energy curves calculated using the Inverted Perturbation Approach method. New rotational perturbations observed and reported in the upper electronic state. Abstract: A new ro-vibrational analysis of the N2 C 3 Π u → B 3 Π g system is performed by high resolution Fourier transform spectroscopy in the visible-UV region. A spectral region between 20, 000 and 50, 000 cm − 1 was covered in this analysis, with a total of 41 bands observed and studied. As a result, new and improved molecular constants were deduced from the attribution of observed spectral lines. With the new constants, potential energy curves were calculated for both states using the IPA method and in possession of these new curves, the Franck-Condon factors and r-centroids were calculated. Strong rotational perturbations were observed, such as spectral line shift and intensity anomalies, notably at the vibrational levels v ′ = 1 and 2 of the C 3 Π u electronic state.